Aspectos fundamentales del acto libre en el pensamiento de Santo Tomás de Aquino - Ponce, Manuel Ocampo (Sapientia, 2014)
God has impressed upon both material and spiritual creatures, including the concrete case of man, a necessary and indefectible direction towards their end. But at the same time, in the corporeal world, the human person possesses a special freedom with regard to the means whereby to reach that end. This is precisely what distinguishes man from irrational animals: that our free and spiritual nature must be directed in its activity by a law specifically distinct from that of the irrational world, such that, while it drives us towards our end, it remains compatible with free will. Given the relevance of this theme for the understanding of the moral problem of the human person, the goal of this work is to delve more deeply into the nature of free human acts and therefore into the foundational principles of free will in the thought of St. Thomas Aquinas, who undoubtedly has offered a profound analysis of human acts.